Implication of Galaxy-scale Negative Feedback by One of the Most Powerful Multiphase Outflows in a Hyperluminous Infrared Galaxy at Intermediate Redshift - Xiaoyang Chen; Masayuki Akiyama; Kohei Ichikawa; Yoshiki Toba; Toshihiro Kawaguchi; Takuma Izumi; Toshiki Saito; Daisuke Iono; Masatoshi Imanishi; Kianhong Lee; Hiroshi Nagai; Hirofumi Noda; et al. (The Astrophysical Journal)
Powerful galactic outflows driven by active galactic nuclei (AGNs) are commonly considered as one of the main mechanisms to regulate star formation in massive galaxies. Ultra- and hyperluminous IR galaxies (U/HyLIRGs) are thought to represent a transition phase of galaxies from a rapidly growing period to a quiescent status as gas is swept out by outflows, providing a laboratory in which to investigate outflows and their feedback effects on hosts. In this paper we report recent Gemini and Atacama Large Millimeter/submillimeter Array (ALMA) observations of a HyLIRG, J1126, at z = 0.46842, which has been identified with a puzzling coexistence of a fast ionized outflow (>2000 km s ^−1 ) and an intense starburst (star formation rate of 800 M _⊙ yr ^−1 ). The Gemini observation shows the fast ionized outflow is extended to several kiloparsecs with a mass-loss rate of 180 M _⊙ yr ^−1 . A massive molecular outflow with a high mass-loss rate (2500 M _⊙ yr ^−1 ) is revealed by ALMA. The multiphase outflows show large factors of momentum boost and loading of kinetic power, indicating a driving by the thermal pressure of a nuclear hot wind and/or the radiation pressure of a highly obscured AGN. In addition to ejection of kinetic energy, it is also found that the powerful outflow can induce an ionizing shock in the galaxy disk and enhance the excitation and dissociation of molecular gas. The powerful outflow probably results in an instantaneous negative feedback and shows potential to regulate host growth in the long term.